Chronic steroid use and readmission following total shoulder arthroplasty - Kenny Ling, BS; Matthew Kim, BA; Alireza Nazemi, MD, MS; Emma Smolev, BA; David E. Komatsu, PhD; Edward D. Wang, MD (JSES International, 2022)
Background: Degenerative arthritis is a major indication for both anatomic and reverse total shoulder arthroplasty (TSA). Degenerative arthritis is an age-related process that can be secondary to mechanical wear or inflammatory or autoimmune diseases, such as rheumatoid arthritis or systemic lupus erythematosus. Management of these diseases can include chronic corticosteroid for their anti-inflammatory and immunosuppressive effects. Given the well-known complications of chronic steroid use on other surgical procedures, investigation into postoperative complications specific to TSA will assist physicians in risk stratification and preoperative planning. The purpose of this study was to investigate the association between chronic preoperative steroid use and postoperative complications following TSA. Methods: The American College of Surgeons National Surgical Quality Improvement database was queried for all patients who underwent TSA between 2015 and 2020. Patient demographics, comorbidities, surgical characteristics, and 30-day postoperative complication data were collected. Multivariate logistic regression was used to identify postoperative complications associated with chronic preoperative steroid use. Reasons and risk factors for readmission among chronic steroid users were subsequently identified, as well. Results: A total of 26,669 patients were included in this study: 25,376 (95.2%) were included in the nonsteroid cohort and 1293 (4.8%) were included in the chronic steroid cohort. The postoperative complications that were significantly associated with chronic preoperative steroid use were septic shock (P = .007), urinary tract infection (P = .016), myocardial infarction (P = .022), ventilator >48 hours (P = .028), readmission (P < .001), nonhome discharge (P < .001), and mortality (P = .007). The only postoperative complication independently associated with chronic preoperative steroid use was readmission (odds ratio, 1.36; 95% confidence interval, 1.04-1.79; P = .027). Conclusion: Preoperative chronic steroid use is an independent predictor for readmission following TSA. As procedural improvement increases surgical volume for TSA, a better understanding of preoperative risk factors can improve perioperative risk stratification and help to minimize adverse outcomes.